Sustainability certifications, environmental disclosures, export volume and technology: the impact on the performance of oil palm plantation companies - Alif Falni Hassan Shukri
Recent environmental issues especially deforestation and wildlife conservation efforts have becoming critical issues for Oil Palm Plantation Companies (OPPC). Malaysia is now subject to exporting only RSPO certified palm oil to the western countries. RSPO stands for Roundtable on Sustainable Palm Oil which was initiated in January 2003 by a private organisation and it is a voluntary exercise. Following that, Malaysia implemented its own certification known as Malaysian Sustainable Palm iJ (MSP in November 2013. The key question is whether these certifications improve the performance of OPPC? Thus, this research examines the relationship between the RSPO certification, MSPO certification, environmental disclosures, export volumes and palm oil technology and the performance of Oppc. Postal and e-mail questionnaire were sent to 317 respondents in OPPC. A total of 108 were returned but five of them were incomplete and thus, not incl uded in the final analysis. A 10-point Likert scale was used to measure the responses. The data was analysed using the Structural Equation Modeling (SEM) and Statistical Package for Social Sciences (SPSS). The study revealed a significant relationship between firm performance and (i) palm oil technology (p-value<0.001); (ii) environmental disclosures (pvalue<0.05); and (iii) export volumes (p-value<0.05). The relationships were insignificant for the RSPO certification (p-value=0.388) and MSPO certification (pvalue=0.917). The research demonstrates that both RSPO and MSPO certifications do not significantly impact the performance of OPPC and thus, should not be mandatory in Malaysia. Furthermore, this study also provides further evidence of the importance of environmental disclosures and technology in improving the performance. Therefore, the practice of environmental disclosures of OPPC should be further enhanced and the investment in palm oil technology should be given a priority by both the industry and the government. Further studies should be conducted to examine sustainability costs and environmental disclosures within the new framework which is integrated reporting.